2018
DOI: 10.1177/0266242617748201
|View full text |Cite
|
Sign up to set email alerts
|

Country-level determinants and consequences of overconfidence in the ambitious entrepreneurship segment

Abstract: Countries vary widely and systematically in the extent to which the ambitions of their entrepreneurs differ from their realisations. We label this discrepancy entrepreneurial overconfidence (EOC). Although a certain level of EOC may be beneficial for an economy, we provide empirical support for the argument that if entrepreneurial ambitions substantially and systematically exceed realisations, this may be at the cost of economic and societal prosperity. Therefore, we need to know more about country levels of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 50 publications
(64 reference statements)
0
28
0
1
Order By: Relevance
“…This is consistent with the analysis of overoptimism (cf. Brieger, Bäro, Criaco, & Terjesen, 2020;Cieślik, Kaciak, & van Stel, 2018), in which young people see more favorable conditions for seizing available opportunities in the market. Contrary to this result, entrepreneurial behavior among students seems to be very low.…”
Section: Empirical Strategy and Estimation Methodsmentioning
confidence: 99%
“…This is consistent with the analysis of overoptimism (cf. Brieger, Bäro, Criaco, & Terjesen, 2020;Cieślik, Kaciak, & van Stel, 2018), in which young people see more favorable conditions for seizing available opportunities in the market. Contrary to this result, entrepreneurial behavior among students seems to be very low.…”
Section: Empirical Strategy and Estimation Methodsmentioning
confidence: 99%
“…Optimism facilitates prompt decision-making while starting new ventures, as well as the drive to obtain the relevant skills and experiences [ 86 ]; the career ambitions of entrepreneurs may inculcate optimism in order to pursue career advancements. Smith et al [ 87 ] found, with regards to an optimistic perspective, that resilience and the negation of women’s glass ceiling beliefs (which could diminish their career ambition) are positively associated with work engagement.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Accordingly, we build two categorical variables ( Perceived social status and Perceived economic status ) on the basis of the answers given by the respondents in rating their economic and social status on a 10-point Likert scale; they vary from 1 (highest relative position) to 10 (lowest relative position). 18 It is worth noticing that although the CPES does not allow us to build measures of self-efficacy (Bandura 1997;Poon et al 2006) or overoptimism (Cieslik et al 2018), the subjective evaluation of the entrepreneurs' status is highly informative. For instance, as suggested by Koryak et al (2015), perceived social status may act as a proxy for a measure of self-esteem.…”
Section: Variables Of Interestmentioning
confidence: 99%